2017
DOI: 10.1016/j.critrevonc.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prehabilitation and rehabilitation including a home-based component on physical fitness, adherence, treatment tolerance, and recovery in patients with non-small cell lung cancer: A systematic review

Abstract: This systematic review aimed to examine physical fitness, adherence, treatment tolerance, and recovery for (p)rehabilitation including a home-based component for patients with non-small cell lung cancer (NSCLC). PRISMA and Cochrane guidelines were followed. Studies describing (home-based) prehabilitation or rehabilitation in patients with NSCLC were included from four databases (January 2000-April 2016, N=11). Nine of ten rehabilitation studies and one prehabilitation study (437 NSCLC patients, mean age 59-72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 51 publications
(247 reference statements)
1
48
0
Order By: Relevance
“…Exercise interventions in lung cancer survivors commonly take place as part of comprehensive, multidisciplinary pulmonary rehabilitation programs, either in the preoperative or postoperative context. 37 Recent systematic reviews suggest that preoperative exercise improves cardiopulmonary fitness 38,39 and may reduce the risk of surgical complications, [40][41][42][43] while postoperative exercise may improve functional and/or exercise capacity and QoL. [42][43][44][45] While these findings provide supporting evidence for exercise in lung cancer survivorship, the authors of the systematic reviews raise concerns for volunteer and selection bias and inadequate sample size for the included studies, and note a lack of large randomized controlled trials (RCTs) of exercise interventions for lung cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise interventions in lung cancer survivors commonly take place as part of comprehensive, multidisciplinary pulmonary rehabilitation programs, either in the preoperative or postoperative context. 37 Recent systematic reviews suggest that preoperative exercise improves cardiopulmonary fitness 38,39 and may reduce the risk of surgical complications, [40][41][42][43] while postoperative exercise may improve functional and/or exercise capacity and QoL. [42][43][44][45] While these findings provide supporting evidence for exercise in lung cancer survivorship, the authors of the systematic reviews raise concerns for volunteer and selection bias and inadequate sample size for the included studies, and note a lack of large randomized controlled trials (RCTs) of exercise interventions for lung cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…37 Recent systematic reviews suggest that preoperative exercise improves cardiopulmonary fitness 38,39 and may reduce the risk of surgical complications, [40][41][42][43] while postoperative exercise may improve functional and/or exercise capacity and QoL. [42][43][44][45] While these findings provide supporting evidence for exercise in lung cancer survivorship, the authors of the systematic reviews raise concerns for volunteer and selection bias and inadequate sample size for the included studies, and note a lack of large randomized controlled trials (RCTs) of exercise interventions for lung cancer survivors. 40,[43][44][45] A more recent RCT 46 examining the impact of physical activity/exercise on fatigue in advanced lung cancer survivors showed no difference compared to usual care; however, in exploratory analyses of 38 (34%) of participants who increased physical activity/exercise during the intervention period, there was a significant reduction in fatigue symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for effectiveness is not as consistent in lung cancer survivors [4]. Recent systematic reviews of exercise interventions in lung cancer survivors suggest that while exercise training can improve functional EC and QoL following curative-intent therapy [24][25][26][27], there are concerns for bias, inadequate sample size, and lack of large randomized controlled trials [24,25,28]. Moreover, a recent systematic review identified numerous patient-related barriers to regular physical activity in lung cancer survivors [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of curative-intent therapy of lung cancer have unique effects on cardiopulmonary health since part of the therapy requires local destruction and/or removal of lung tissue which may impede function and EC in some patients. Therefore, lung cancer survivors face unique health challenges that may make typical exercise interventions inaccessible [27]. The characterization of dyspnea may provide important insights into effective strategies to improve physical exercise in this group of cancer survivors.…”
Section: Discussionmentioning
confidence: 99%